Työolojen kolme vuosikymmentä : työolotutkimusten tuloksia 1977-2008 - Lehto, Anna-Maija; Sutela, Hanna (Tilastokeskus, 2008)
Työolotutkimus 2008
Keywords: tilastot; työolot; työelämä; Työmarkkinat; Työolot